(untitled) (Swiss Medical Weekly, 2018)
Shigella sonnei causes foodborne infections, but has recently also been described as a sexually transmitted infection (STI), with increased levels of antimicrobial resistance. We describe three cases of sexually acquired Shigella sonnei infection – the first report of this emerging infection in Switzerland. We used in-house whole genome sequencing (WGS) to investigate possible transmission routes and epidemiological correlations between the three cases. The genomic analysis demonstrated that two of three case isolates were very closely related, with only two single nucleotide polymorphism differences between them, despite being isolated from two unrelated patients at time-points six months apart, and the infections having been acquired at different geographic locations within Europe. All three isolates were found to fall within two of the clusters (1 and 7) defined within UK men who have sex with men (MSM) isolate populations, but with higher divergence, suggesting a more diverse pool circulating within Europe. Phenotypic testing confirmed the genotypic findings, with all three isolates azithromycin resistant, and two out of three resistant to quinolones. This report underlines the importance of the implementation of new sequencing technologies in the investigation of epidemiological aspects of this STI circulating in the population of MSM. In such cases, therapy should always be guided by antimicrobial susceptibility testing owing to increasing resistances. Greater awareness of this emerging sexually transmitted infection is needed.